2023
DOI: 10.1021/acs.jmedchem.2c01808
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Benzoselenazole Derivatives as Potent and Selective c-MYC Transcription Inhibitors

Abstract: Developing c-MYC transcription inhibitors that target the G-quadruplex has generated significant interest; however, few compounds have demonstrated specificity for c-MYC G-quadruplex and cancer cells. In this study, we designed and synthesized a series of benzoazole derivatives as potential G-quadruplex ligand-based c-MYC transcription inhibitors. Surprisingly, benzoselenazole derivatives, which are rarely reported as G-quadruplex ligands, demonstrated greater c-MYC G-quadruplex selectivity and cancer cell spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This presents a significant challenge in the development of c-MYC G4 stabilizers. Fortunately, experimental evidence has confirmed that the binding affinity of the same compound to G4 structures of different genes varies [11,13,17]. Therefore, the development of a drug with high selectivity for c-MYC G4 structure and robust anti-tumor activity holds promise as a reliable choice for TNBC therapy, bearing crucial significance in improving the prognosis of TNBC patients [12].…”
Section: Challenges Encountered In the Development Of C-myc G4 Stabil...mentioning
confidence: 99%
“…This presents a significant challenge in the development of c-MYC G4 stabilizers. Fortunately, experimental evidence has confirmed that the binding affinity of the same compound to G4 structures of different genes varies [11,13,17]. Therefore, the development of a drug with high selectivity for c-MYC G4 structure and robust anti-tumor activity holds promise as a reliable choice for TNBC therapy, bearing crucial significance in improving the prognosis of TNBC patients [12].…”
Section: Challenges Encountered In the Development Of C-myc G4 Stabil...mentioning
confidence: 99%
“…G-quadruplex is a highly stable four-stranded nucleic acid secondary structure formed by guanine (G)-rich DNA or RNA sequences. , Extensive research reveals that G-rich sequences, adopting G-quadruplex structures, are prevalent within many key functional regions in the genome and transcriptome such as telomeres, promoter regions of some oncogenes, and untranslated regions of mRNA. More importantly, the folding and unfolding of G-quadruplex structures are dynamic processes similar to a molecular switch, which participates in the regulation of various important biological processes such as telomere protection, DNA replication and transcription, and mRNA translation. Recent studies have demonstrated that the 5′-untranslated region (5′-UTR) of KRAS mRNA harbors several quadruplex-forming motifs able to form local rG4 structures, termed utr-z, utr-1, and utr-c . A substantial body of evidence has supported that G4-forming sequences in 5′-UTR can function as repressors of translation initiation and protein expression. , RNA helicases, such as eIF4A and DHX36, can unwind KRAS rG4s and rescue the protein expression of KRAS. Therefore, small molecules targeting KRAS rG4s have potential to inhibit KRAS translation, consequently impeding the activation of KRAS signaling.…”
Section: Introductionmentioning
confidence: 99%
“…29 Benzoselenazole 7 was developed by Tan and co-workers as potential G-quadruplex ligand-based c-MYC transcription inhibitors, promising target for cancer therapy. 30 The Se analogue 8 of ritonavir has shown anti-HIV activity comparable to that of parent molecules together with reduced cytotoxicity and improved selectivity index. 31 Having great pharmaceutical and other applications, substituted benzoselenazoles are found to be significant frameworks of Se containing heterocycles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fluselenamyl 6 has been investigated for the treatment of Alzheimer’s Disease and could be available as a commercial drug in the near future . Benzoselenazole 7 was developed by Tan and co-workers as potential G-quadruplex ligand-based c-MYC transcription inhibitors, promising target for cancer therapy . The Se analogue 8 of ritonavir has shown anti-HIV activity comparable to that of parent molecules together with reduced cytotoxicity and improved selectivity index .…”
Section: Introductionmentioning
confidence: 99%